Molecular longitudinal tracking of Mycobacterium abscessus spp. during chronic infection of the human lung. - Kaj M Kreutzfeldt; Paul R McAdam; Pauline Claxton; Anne Holmes; A Louise Seagar; Ian F Laurenson; J Ross Fitzgerald (PLoS ONE)
The Mycobacterium abscessus complex is an emerging cause of chronic pulmonary infection in patients with underlying lung disease. The M. abscessus complex is regarded as an environmental pathogen but its molecular adaptation to the human lung during long-term infection is poorly understood. Here we carried out a longitudinal molecular epidemiological analysis of 178 M. abscessus spp. isolates obtained from 10 cystic fibrosis (CF) and 2 non CF patients over a 13 year period. Multi-locus sequence and molecular typing analysis revealed that 11 of 12 patients were persistently colonized with the same genotype during the course of the infection while replacement of a M. abscessus sensu stricto strain with a Mycobacterium massiliense strain was observed for a single patient. Of note, several patients including a pair of siblings were colonized with closely-related strains consistent with intra-familial transmission or a common infection reservoir. In general, a switch from smooth to rough colony morphology was observed during the course of long-term infection, which in some cases correlated with an increasing severity of clinical symptoms. To examine evolution during long-term infection of the CF lung we compared the genome sequences of 6 sequential isolates of Mycobacterium bolletii obtained from a single patient over an 11 year period, revealing a heterogeneous clonal infecting population with mutations in regulators controlling the expression of virulence factors and complex lipids. Taken together, these data provide new insights into the epidemiology of M. abscessus spp. during long-term infection of the CF lung, and the molecular transition from saprophytic organism to human pathogen.